In-situ screening of high-yielding maize (Zea mays) for climate resilience in the semi-arid tropics of East Nusa Tenggara, Indonesia - ERLANGGA DWI ATMOJO; SHANASYA NAJWA DEVYA ASYARI; AZERI GAUTAMA ARIFIN; ARIFIN NOOR SUGIHARTO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Atmojo ED, Asyari SND, Arifin AG, Sugiharto AN. 2025. In-situ screening of high-yielding maize (Zea mays) for climate resilience in the semi-arid tropics of East Nusa Tenggara, Indonesia. Biodiversitas 26: 6427-6436. Developing climate-resilient maize (Zea mays) is crucial for ensuring food security in Indonesia's semi-arid regions, particularly in East Nusa Tenggara, where recurring droughts severely impact maize productivity. Maize farming in these areas faces extreme environmental challenges, highlighting the need for varieties capable of thriving under water-limited conditions. This study evaluated the performance of ten top-cross maize hybrids (UB 21-UB 30), derived from elite S3 inbred lines, under semi-arid conditions, comparing them to two commercially available varieties as controls. Genetic parameters were calculated from variance components, phenotypic variation was assessed using analysis of variance, and superior hybrids were identified through hierarchical clustering and Genotype × Trait (GT) analysis. The studied traits showed medium to high heritability, with low to moderate genotypic and phenotypic coefficients of variation. UB 25 emerged as the top performer, with a potential yield of 6.39 t ha⁻¹, surpassing the best commercial variety. This hybrid also demonstrated significant drought resilience, characterized by a shorter anthesis-silking interval and fewer unfilled tips, both of which are essential for maintaining yield stability under drought stress. Additionally, UB 28 was identified as another promising hybrid, exhibiting high yield potential and favorable stress-adaptive traits. These results underscore the importance of in-situ screening to identify maize varieties tailored to the specific challenges of semi-arid environments. The hybrids identified in this study provide a strong foundation for developing drought-resilient maize in Indonesia's semi-arid tropics.